2015
DOI: 10.1186/s12870-015-0675-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of maize kernel starch content revealed by high-density single nucleotide polymorphism markers in a recombinant inbred line population

Abstract: BackgroundStarch from maize kernels has diverse applications in human and animal diets and in industry and manufacturing. To meet the demands of these applications, starch quantity and quality need improvement, which requires a clear understanding of the functional mechanisms involved in starch biosynthesis and accumulation. In this study, a recombinant inbred line (RIL) population was developed from a cross between inbred lines CI7 and K22. The RIL population, along with both parents, was grown in three envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 85 publications
0
34
0
Order By: Relevance
“…The starch content is similar to the main sources of starch used for biofuels, including cereals (60-80% starch), legumes (25-50% starch), tubers and roots (60-90% starch), and green and immature fruits (as much as 70% starch) [16,17]. The main crops used are sorghum, wheat, cassava, potatoes, and sweet potatoes [16,18,19], in addition to maize, which is the most widely-used starch Energies 2017, 10, 1574 4 of 10 crop for bioethanol production and has a starch content ranging from 60 to 85% depending on the variety [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…The starch content is similar to the main sources of starch used for biofuels, including cereals (60-80% starch), legumes (25-50% starch), tubers and roots (60-90% starch), and green and immature fruits (as much as 70% starch) [16,17]. The main crops used are sorghum, wheat, cassava, potatoes, and sweet potatoes [16,18,19], in addition to maize, which is the most widely-used starch Energies 2017, 10, 1574 4 of 10 crop for bioethanol production and has a starch content ranging from 60 to 85% depending on the variety [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…For crude protein and amino acid measurements, the total protein (crude protein) was extracted from kernel, embryo and endosperm, hydrolyzed into amino acids and then used for subsequent analysis by liquid phase chromatography. Measurement of carbohydrate in endosperm was as previously described (Wang et al ). Measurement of lipids in the kernel was performed, as previously described (Li et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Oil, starch, and protein content directly affect the quality of food and feed (Baker et al, 1969; Lewis et al, 1982; Worral et al, 2015). Maize is also a popular fuel source, as its starch content has become important in the production of ethanol, potentially creating bottlenecks in the stable supply of sufficient maize for food, feed, and fuel (Ray et al, 2013; Wang et al, 2015). Balancing maize kernel composition for both food and fuel use is an even greater challenge, as altering kernel composition greatly impacts yield (Bjarnason and Vasal, 1992; Worral et al, 2015).…”
mentioning
confidence: 99%
“…Shrunken1 , shrunken2 , brittle2 , waxy1 , sugary2 , dull1 , amylose extender1 , and sugary1 (Hennen‐Bierwagen and Myers, 2013; Huang et al, 2014; Klösgen et al, 1986) are a few of the known genes involved in starch biosynthesis. However, little is known about the connections of these genes in the regulation of starch biosynthesis and starch accumulation in maize (Wang et al, 2015). Many QTL studies have been conducted to further explain the connections of known maize starch genes to their actual roles in starch biosynthesis in the maize kernel (Cook et al, 2012; Dudley et al, 2007, 2004; Goldman et al, 1993; Guo et al, 2013) with few causative genetic factors having been found (Wang et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation